1991
DOI: 10.1152/ajpendo.1991.260.5.e727
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor induces skeletal muscle protein breakdown in rats

Abstract: The metabolic response to infection includes loss of lean tissue and increased nitrogen excretion. The loss of muscle tissue during infection results in large part from accelerated skeletal muscle protein breakdown. Recent studies suggest that macrophage-derived products secreted during infection may signal increased muscle proteolysis. To test this, in the present report the ability of interleukin (IL-1) and tumor necrosis factor (TNF) to enhance muscle proteolysis was examined. Young rats were injected intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
137
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 9 publications
9
137
0
2
Order By: Relevance
“…Skeletal muscle fibers have been shown to produce TNFα in a fiber type specific manner in both humans (Plomgaard et al, 2005) and rats (Phillips and Leeuwenburgh, 2005). TNFα is associated with accelerated skeletal muscle protein loss both in vitro (Li and Reid, 2000) and in vivo (Flores et al, 1989;Goodman, 1991). In the present study, we found that the absence of IL-10 was associated with a significantly greater plasma TNFα response, but that this did not extend to an increase in skeletal muscle content of TNFα.…”
Section: Discussionsupporting
confidence: 39%
“…Skeletal muscle fibers have been shown to produce TNFα in a fiber type specific manner in both humans (Plomgaard et al, 2005) and rats (Phillips and Leeuwenburgh, 2005). TNFα is associated with accelerated skeletal muscle protein loss both in vitro (Li and Reid, 2000) and in vivo (Flores et al, 1989;Goodman, 1991). In the present study, we found that the absence of IL-10 was associated with a significantly greater plasma TNFα response, but that this did not extend to an increase in skeletal muscle content of TNFα.…”
Section: Discussionsupporting
confidence: 39%
“…tumour necrosis factor-a (TNF-a)) have also been implicated in the skeletal muscle atrophy of several physiological/ pathological states. 37,38 In animals treated with exogenous TNF-a 38,39 or expressing a transgene, 40 losses in muscle mass are observed. Moreover, Buck and Chojkier 39 reported structural irregularities consisting of smaller fibres in skeletal muscles from mice receiving exogenous TNF-a.…”
Section: Iiamentioning
confidence: 99%
“…Muscle structure and cell surface and extracellular cytoskeleton up-regulated genes found in both JDM and DMD, including embryonic myosin heavy chain (52.5-fold), myosin-binding protein H (71.3-fold), skeletal muscle perinatal myosin heavy chain MYH8 (13.9-fold), nicotinic acetylcholine receptor ␣ subunit (12.2-fold), thrombospondin-4 (8.2-fold), prepro-␣2 (I) collagen (7.4-fold), and chondroitin sulfate proteoglycan versican (Ïł5-fold). TNF-␣ release is a feature of necrotic muscle, and TNF-␣ itself damages skeletal muscle (43).…”
Section: Degeneration/regeneration Cascades Expressed By Necrotic Myomentioning
confidence: 99%